Law No. 10 of the year 2018 Promulgating the law on The Rights of Persons with disabilities = قانون حقوق الأشخاص ذوي الإعاقة. (2025)
Law no. 10 of the year 2018 promulgating the law on the rights of persons with disabilities – part 1: general provisions – part 2: health rights of the persons with disabilities – part 3: right to education – part 4: occupational preparation, training and right to work – part 4: community treatment, legal and criminal protection of the persons with disabilities – part 6: political and trade union rights of the persons with disabilities – part 7: culture, sports and recreation – part 8: penalties قانون رقم 10 لسنة 2018 بإصدار قانون حقوق الأشخاص ذوى الاعاقة – الباب الأول أحكام عامة – الباب الثانى الحقوق الصحية للأشخاص ذوى الاعاقة – الباب الثالث الحق فى التعليم – الباب الرابع الإعداد المهنى والتدريب والحق فى العمل – الباب الخامس المعاملة المجتمعية – الباب السادس الحقوق السياسية والنقابية للأشخاص ذوى الاعاقة – الباب السابع الثقافة والرياضة والترويح – الباب الثامن العقوبات